Combination of Breast Care and Moringa Leaf Tea to Increase Breast Milk Volume - Arie Maineny; Taqwin Taqwin; Putri Mulia Sakti (Universitas Aisyah Pringsewu, 2023)
A small amount of breast milk at the beginning of breastfeeding is one of the problems that mothers often experience during the puerperium. Caring for the breasts during pregnancy can help produce milk. Moringa leaf tea can help breast milk production because it contains phytosterol chemicals which have the effect of Lagtogogum, in increasing milk production. The purpose of the study was to determine the combination of breast care and Moringa leaf tea in increasing the volume of breast milk. The design of this study was a pre-experimental one-group pre-test and post-test. Purposive sampling was used to take samples of postpartum mothers on the first day. Wilcoxon test was used in univariate and bivariate analysis. The results of the study on 15 respondents, 2 (13.3%) breast milk production was smooth and 13 (86.7%) was not smooth before getting breast care and Moringa leaf steeping water. Smooth milk production 13 (86.7%), and 2 (13.3%) substandard, after receiving breast care and Moringa leaf tea. Wilcoxon test value of P = 0.001 (p less than 0.05). Postpartum mothers produce more milk on the first day when they combine breast care with Moringa leaf tea. Abstrak: ASI yang sedikit pada awal menyusui merupakan salah satu masalah yang sering dialami ibu pada masa nifas. Merawat payudara saat hamil dapat membantu produksi ASI. Teh daun kelor dapat membantu produksi ASI karena mengandung zat kimia fitosterol yang memiliki efek Lagtogogum, dalam meningkatkan produksi ASI. Tujuan penelitian untuk mengetahui kombinasi perawatan payudara dan teh daun kelor dalam meningkatkan volume ASI. Desain penelitian ini adalah pre-experimental one group pre-test and post-test. Purposive sampling digunakan untuk mengambil sampel ibu nifas pada hari pertama. Uji Wilcoxon digunakan dalam analisis univariat dan bivariat. Hasil penelitian terhadap 15 responden, 2 (13,3%) produksi ASI lancar dan 13 (86,7%) tidak lancar sebelum mendapatkan perawatan payudara dan air seduhan daun kelor. Produksi ASI lancar 13 (86,7%), dan 2 (13,3%) kurang lancar, setelah mendapat perawatan payudara dan teh daun kelor. Uji Wilcoxon nilai P = 0,001 (p kurang dari 0,05). Ibu nifas menghasilkan lebih banyak ASI pada hari pertama ketika mereka menggabungkan perawatan payudara dengan teh daun kelor.